STUDY OF THE SET OF CONTINUOUS SOLUTIONS OF SYSTEMS OF LINEAR DIFFERENCE-FUNCTIONAL EQUATIONS WITH CONSTANT COEFFICIENTS - Єрьоміна, Тетяна; Поварова, Олена; Козак, Валентина (SWorldJournal, 2025)
Conditions for the existence of continuous solutions to a certain class of systems of linear difference-functional equations with constant coefficients are obtained in the case when the eigenvalues of the system’s coefficient matrix are real and negative